Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd003971.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Methadone for cancer pain

Abstract: There is evidence to suggest that methadone is an analgesic with similar efficacy to morphine and a comparable side effect profile. However, the majority of studies involved single dose comparisons or short term use. This methodology fails to reproduce clinical practice. Therefore there is a very significant danger that the effects of methadone accumulation leading to delayed onset of adverse effects which occurs with chronic administration has not been represented. Fixed interval dosing schedules conducted ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(34 citation statements)
references
References 61 publications
1
31
0
2
Order By: Relevance
“…12,13 Methadone is a unique synthetic opioid with activity at both m-receptors, and N-methyl-D-aspartate receptors, 14 which are implicated in the development of neuropathic pain. Two systematic reviews 15,16 have examined the use of methadone for cancer-related pain. Four studies that compared methadone to other oral or transdermal strong opioids 17e20 found that methadone provides similarly effective analgesia as morphine sulfate, oxycodone, and hydromorphone and is associated with no more side effects than these opioids.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Methadone is a unique synthetic opioid with activity at both m-receptors, and N-methyl-D-aspartate receptors, 14 which are implicated in the development of neuropathic pain. Two systematic reviews 15,16 have examined the use of methadone for cancer-related pain. Four studies that compared methadone to other oral or transdermal strong opioids 17e20 found that methadone provides similarly effective analgesia as morphine sulfate, oxycodone, and hydromorphone and is associated with no more side effects than these opioids.…”
Section: Introductionmentioning
confidence: 99%
“…Morphine is metabolized to morphine-3-glucuronide (M3G) and the active morphine-6-glucuronide (M6G) via UGT2B7 [6]. It is commonly cited that the interindividual variability of the pharmacokinetics of methadone is larger than for other opioids [7].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, its demonstrated clinical efficacy and cost-effectiveness have made methadone an increasingly prescribed opioid, particularly in treating moderate-to-severe pain (211,212). Methadone consists of a racemic mix of R-and S-methadone (213), though the Risomer is believed to account for its opioid effects (214).…”
Section: Methadonementioning
confidence: 99%